CITRA MANUSIA DALAM KUMPULAN CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Bambang Lelono (Jurnal Lingua Idea, 2015)
Collection of short stories Senyum Karyamin when analyzed by sociology of literature has several characteristics or aspects of sociocultural (Java man) which is prominent coloring its thirteen short stories. These aspects are the religious aspect, which is about the religious attitude of human beings. It can be seen in the short story of Syukuran Sutabawor. Moral aspects, including human dignity and kamanungsan be seen on Ah,Jakarta short story and Syukuran Sutabawor short story. The fatalistic and nrimo aspects contained in short story Senyum Karyamin. Aspects of prasojo and aja dumeh seen in short stories Senyum Karyamin, Ah,Jakarta, and Kenthus.In addition to the sociocultural characteristics, image or picture in a collection of short stories this Senyum Karyamin, involving directly the values of its sociocultures namely: harmony, love and brotherhood, compassion, moral purity, human dignity, and so on. Those values are strong enough coloring short stories collected in Senyum Karyamin.